Methane emission from Matsuo rice paddy field in light of different fertilizers, costs, profit and carbon credit - Kun, Gergő; Nagy, Adrián; Shunsuke, Hanazawa; Maasa, Takahashi; Kazuyuki, Inubushi (Acta Agraria Debreceniensis, 2016)
Nowadays global warming is a major issue to our environment. This issue is generated by the modern human activities like industry and intensive agriculture. This research is about methane emission from rice paddy fields. The aim of the study is to lower the methane emission from the field with the help of using different type of fertilizers, whilst we keep in focus the efficient economic operation. The main experimental field is Matsuo paddy field, (Matsuo town, Sanbu city, Chiba prefecture) which is analyzed by the Chiba University’s soil science laboratory, they provided the data for this study. During the study three type of fertilizer was analyzed which are all organic and the control was a regular chemical fertilizer. For all fertilizers the cost and income of the production were calculated and the profit was weighted with the methane emission what a specific fertilizer produced during the cultivation. In the future if the organic fertilizers are in focus than it is necessary to find a new material what can be competitive with the chemical fertilizers in focus of GHG emission or find an alternative way of the usage of methane in biogas production.